2022
DOI: 10.3389/fnins.2022.701632
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Classification of Parkinsonian and Essential Tremors for Diagnosis Using Machine Learning Algorithms

Abstract: Due to overlapping tremor features, the medical diagnosis of Parkinson’s disease (PD) and essential tremor (ET) mainly relies on the clinical experience of doctors, which often leads to misdiagnosis. Seven predictive models using machine learning algorithms including random forest (RF), eXtreme Gradient Boosting (XGBoost), support vector machine (SVM), logistic regression (LR), ridge classification (Ridge), backpropagation neural network (BP), and convolutional neural network (CNN) were evaluated and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…This is to make each feature comparatively similar in magnitude, allowing ML algorithms based on gradient descent to iterate/converge more smoothly. Some authors used standardization to scale the features to ensure comparability between ML model performance, 32 whereas others normalized, minimum to maximum, their power‐spectrum density (PSD)–based features before implementing a two‐stage algorithm 46 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is to make each feature comparatively similar in magnitude, allowing ML algorithms based on gradient descent to iterate/converge more smoothly. Some authors used standardization to scale the features to ensure comparability between ML model performance, 32 whereas others normalized, minimum to maximum, their power‐spectrum density (PSD)–based features before implementing a two‐stage algorithm 46 …”
Section: Discussionmentioning
confidence: 99%
“…As tremor intensity physiologically fluctuates with time, the recording length governs which temporal aspects of the signal are included in the analysis. For most studies, the length per tremor signal recorded ranged from 20 38,82 to 30 32 to 60 seconds, 51 representing common clinical examination durations. Whereas some studies suggested that differentiation accuracy plateaus with recording lengths from 5 seconds upward, 58 other studies for tremor detection “in‐the‐wild” analyzed data collected over up to 26 hours per patient 62 …”
Section: Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations